The importance of Ki-67 proliferation index in small cell lung cancer - Seda Beyhan Sağmen; Coşkun Doğan; Sevda Cömert; Nesrin Kıral; Elif Torun Parmaksız; Ali Fidan; Nagehan Ozdemir Barisik; Sule Karabulut Gul (The Egyptian Journal of Bronchology)
Abstract Background As in numerous cancers, the connection between the Ki-67 proliferation index and response to treatment in cellular breakdown in the lungs is underlined. The purpose of this study was to investigate the connection between the Ki-67 proliferation index and radiotherapy’s therapeutic and survival effects in small cell lung cancer. Methods The limited-stage small cell lung cancer patients in our hospital were retrospectively reviewed. Patients receiving standard chemoradiotherapy were included in the study. Age, sex, cancer stage, comorbidities, response to treatment, and survival time were recorded. Bronchoscopic or transthoracic lung biopsy specimens which were taken at the time of diagnosis were stained with the Ki-67 immunohistochemical stain. Survival of patients and treatment response were compared statistically with the Ki-67 values. Results The Ki-67 proliferation index (62.29 ± 7.52) was lower in patients with partial response than in patients with complete response (77.08 ± 2.84) (p < 0.001). When the correlation between survival time and Ki-67 was examined, there was a positive correlation between the Ki-67 and survival time (p: 0.019; r: 0.426). The patients were divided into two groups: Ki-67 < 68.70 and Ki-67 ≥ 68.70. In patients with Ki-67 ≥ 68.70, the survival rate was better than that of patients with Ki-67 < 68.70 (p: 0.012). In Cox regression analysis, Ki-67 PI < 68.7 was found that increased mortality by 2742 times independently. Conclusions Patients with a high Ki-67 had a better survival effect than those with low Ki-67, and patients with complete responses had a higher Ki-67 value.